STRATEGI ADAPTASI BUDAYA KOMUNITAS HINDU BALI DALAM MASYARAKAT MULTIKULTURAL DI PATOMAN, BANYUWANGI - Sutrisno, Nanang Sutrisno; A.A. Ngurah Anom Kumbara (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
This study aims to reveal the underlying values, forms, and implications of the cultural adaptation strategies of the Bali Hindu community within the multicultural society in Patoman, Banyuwangi. The research was conducted qualitatively with an ethnographic approach based on the theory of cultural adaptation and social harmony. This study finds that the values that underlie the cultural adaptation strategy of the Bali Hindu community within the multicultural society in Patoman include Tri Hita Karana, Tat Tvam Asi, Manyama Braya, and Bhinneka Tunggal Ika. Forms of cultural adaptation strategy include strengthening socio-cultural and religious identities internally and developing external consolidation by mediating seven universal categories of culture in their social interactions. The implications of the cultural adaptation strategy include the formation of a “Bali Patoman Village” with a distinctive cultural and religious identity, the maintenance of social harmony in a pluralistic society, and the affirmation of a multicultural society structure marked by the coronation of Patoman Village as a “Kampung Pancasila”.